Perancangan Sistem Pengamanan Data Transaksi Pada Database Terdistribusi Menggunakan Metode Hashing - Agung Pambudi; Ari Kusyanti; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In e-commerce, payment outlets are needed as intermediaries, so that purchase can be processed. One of e-commerce in Indonesia is owned by PT. Kereta Api Persero Tbk. The interconnection of transactions on several payment outlets requires a database distribution. This will cause new problems, because the database has a security gap, namely the possibility of transaction data manipulation. Therefore a system that can guarantee transaction data cannot be manipulated is needed. The hashing method is used to calculate the digest value of incoming transactions from payment outlets. Then, the digest value will be sent in turn with transaction data to the online ticket server. Afterward, the digest value from the previous transaction and the latest transaction will be recalculated and resulting a new digest value. This proces is repeated until a hashing chain is created. In this way the payment records will be the same and each data record will be bound. Hence, changing one data record transaction, will damage the composition of the other transaction data records. The composition of a valid data record will be an indication of data integrity of data transaction. This system is implemented successfullywith execution time of every record calculation takes approximatelly 5 seconds.